2020
DOI: 10.3390/pharmaceutics12070600
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interaction between Sorafenib and Atorvastatin, and Sorafenib and Metformin in Rats

Abstract: The tyrosine kinase inhibitor sorafenib is the first-line treatment for patients with hepatocellular carcinoma (HCC), in which hyperlipidemia and type 2 diabetes mellitus (T2DM) may often coexist. Protein transporters like organic cation (OCT) and multidrug and toxin extrusion (MATE) are involved in the response to sorafenib, as well as in that to the anti-diabetic drug metformin or atorvastatin, used in hyperlipidemia. Changes in the activity of these transporters may lead to pharmacokinetic interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…The t 1/2 was approximately 6.83–14.12 h with a gradual decrease process. The pharmacokinetic properties of SOR in rats in our present findings seem to be consistent with other studies ( Paul et al, 2019 ; Karbownik et al, 2020 ). In addition, what is interesting in these data is that the pharmacokinetic profiles of SOR have been showed marked gender-specific differences.…”
Section: Discussionsupporting
confidence: 94%
“…The t 1/2 was approximately 6.83–14.12 h with a gradual decrease process. The pharmacokinetic properties of SOR in rats in our present findings seem to be consistent with other studies ( Paul et al, 2019 ; Karbownik et al, 2020 ). In addition, what is interesting in these data is that the pharmacokinetic profiles of SOR have been showed marked gender-specific differences.…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, our limited sampling strategy (two sampling points at 2 and 6 h after administration) is a limiting factor to draw any conclusion about the pharmacokinetic interaction between metformin and sorafenib and this point deserves further characterization. According to the results of Karbownik et al (Karbownik et al, 2020), we should have expected a lower total exposure to sorafenib in our murine model cotreated with metformin. However, coadministration of sorafenib plus metformin was associated with a greater decrease in tumor volume compared to sequential therapy in our model, which suggests that the differential effects between the two regimens may be the result of pharmacodynamic rather than pharmacokinetic interactions.…”
Section: Discussionmentioning
confidence: 59%
“…Prior administration of metformin impacted neither the plasma concentrations of sorafenib 2 and 6 h after its administration, nor the intracellular bioavailability of sorafenib in HCC cells in vitro. Karbownik et al (Karbownik et al, 2020) recently showed that the concomitant administration of metformin (100 mg/kg) increases the clearance of sorafenib (100 mg/kg) in rats, which results in a lower sorafenib half-life (16.3 ± 3.7 vs 21.9 ± 7.8 h, p=0.0372). This result was obtained from complete sorafenib pharmacokinetics including sampling points up to 96 h. The difference was particularly significant during the terminal elimination phase (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important aspect of the eventual use of sorafenib in NASH is the potential pharmacological interactions with antidiabetic or antihypertensive drugs that are commonly prescribed in NASH patients. Recently, Karbownik et al [ 115 ] investigated the pharmacokinetic interactions between sorafenib and metformin or atorvastatin in a rat model. The concomitant administration of sorafenib and metformin increases the clearance of sorafenib in rats, which results in a significantly lower sorafenib half-life (16.3 vs. 21.9 h).…”
Section: Discussionmentioning
confidence: 99%